1995
DOI: 10.1149/1.2044212
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the AC Impedance of Conducting Polymer Films Studied as Electrode‐Supported and Freestanding Membranes

Abstract: The ac impedance response of a symmetrically bathed membrane consisting of a conducting polymer is modeled. The model is an extension of a recent one proposed for a conducting polymer film contacting an electronic and an ionic conductor on its two faces (modified electrode geometry) and takes into account both diffusion-migration of ionic and electronic charge carriers inside the film and charge-transfer across metal/polymer and polymer/electrolyte interfaces. The membrane impedance is .calculated for various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(37 citation statements)
references
References 6 publications
(8 reference statements)
2
35
0
Order By: Relevance
“…This quantity can be correlated at least qualitatively with the susceptibility to cracking. However, not only the sulfate content but also the material condition (e.g., the degree of cold work) has been found to have an impact on actual crack growth rates [20,23]. Thus, the oxide film properties alone cannot be regarded as determining crack propagation rates.…”
Section: Conventional Thin Layer Contactmentioning
confidence: 99%
See 2 more Smart Citations
“…This quantity can be correlated at least qualitatively with the susceptibility to cracking. However, not only the sulfate content but also the material condition (e.g., the degree of cold work) has been found to have an impact on actual crack growth rates [20,23]. Thus, the oxide film properties alone cannot be regarded as determining crack propagation rates.…”
Section: Conventional Thin Layer Contactmentioning
confidence: 99%
“…An alternative that has been extensively developed is introducing impedance measurements in different configurations to determine the respective contributions of the bulk transport and interfacial transfer processes in the overall impedance response of thin films [23][24][25]. This approach was extended for supercritical temperatures in the present NERI project [3,4].…”
Section: Symmetrical and Asymmetrical Configurations For In Situ Studmentioning
confidence: 99%
See 1 more Smart Citation
“…Also it was reported that Poly(Py) contribute to the strength of composite [42]. Electrochemical Impedance Spectroscopy (EIS) was used as a spectroscopic technique to analyze electrochemical process occurring at the electrolyte/electrode interface and to investigate the charge transfer, ion diffusion and capacitor behavior of conducting polymer modified electrodes [46][47][48]. In the literature, the capacitive features of carbon fiber (CF) electrodes modified by conducting polymer such as poly(N-methyl pyrrole) [45], polythiophene and poly(N-methylpyrrole) [49], Npyrrole, N-phenylpyrrole, and 1[4-methoxyphenyl]-1H-pyrrole homopolymers [50], poly(3-dodecylthiophene) [48], poly(3-methylthiophene) [51], poly(thiophene-imidazole) [52], were characterized by EIS.…”
Section: Introductionmentioning
confidence: 99%
“…Conducting polymers which were coated electrochemically onto CFMEs were studied in detail and reported by Sarac and coworkers [16,[26][27][28][29][30][31][32][33]. Electrochemical impedance spectroscopy (EIS) is a powerful technique to study charge transfer, ion diffusion and capacitance of conducting polymer modified electrodes [34][35][36][37][38][39]. EIS has been used to develop equivalent electric circuits to describe the electrochemical properties of films of conducting polymers in organic solution [40][41].…”
Section: Introductionmentioning
confidence: 99%